(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2022)
The devastating earthquake of 2015 in Nepal overwhelmed the Nepal government which resulted in the government seeking help from the international community. The call from the Nepal government was responded to quickly by many countries. While the government accepted the help from far countries, the Nepal government rejected the humanitarian aid offered by Taiwan saying that Nepal only takes such aid from its neighboring countries. This paper examines the reasons behind the aid rejection of Taiwan by Nepal and also tries to answer what could have happened if it was accepted. Though Nepal is one of the Least Developed countries, even during the disaster time, the aid was rejected. The paper concludes that, even during the most crucial time, there is politics in accepting aid. Nepal’s rejection of Taiwan’s aid was because of the pressure to obey the diplomatic relation with China as Nepal is dependent on China but not on Taiwan. Key words: Nepal, Taiwan, humanitarian aid, earthquake, China, diplomatic relation